Dermatophyte-host relationship of a murine model of experimental invasive dermatophytosis - Venturini, James [UNESP]; Alvares, Anuska Marcelino; Camargo, Marcela Rodrigues de [UNESP]; Marchetti, Camila Martins [UNESP]; Fraga-Silva, Thais Fernanda de Campos [UNESP]; Luchini, Ana Carolina; Arruda, Maria Sueli Parreira de [UNESP] (Elsevier B.V., 2012)
Recognizing the invasive potential of the dermatophytes and understanding the mechanisms involved in this process will help with disease diagnosis and with developing an appropriate treatment plan. In this report, we present the histopathological, microbiological and immunological features of a model of invasive dermatophytosis that is induced by subcutaneous infection of Trichophyton mentagrophytes in healthy adult Swiss mice. Using this model, we observed that the fungus rapidly spreads to the popliteal lymph nodes, spleen, liver and kidneys. Similar to the human disease, the lymph nodes were the most severely affected sites. The fungal infection evoked acute inflammation followed by a granulomatous reaction in the mice, which is similar to what is observed in patients. The mice were able to mount a Th1-polarized immune response and displayed IL-10-mediated immune regulation. We believe that the model described here will provide valuable information regarding the dermatophyte-host relationship and will yield new perspective for a better understanding of the immunological and pathological aspects of invasive dermatophytosis. (c) 2012 Institut Pasteur. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Dermatophytes; Invasive dermatophytosis; Trichophyton mentagrophytes; Cellular immune response; Experimental dermatophytosis